Transthyretin and BRICHOS: The Paradox of Amyloidogenic Proteins with Anti-Amyloidogenic Activity for Aβ in the Central Nervous System - Buxbaum, Joel N.; Johansson, Jan (Frontiers in Neuroscience, 2017)
Amyloid fibrils are physiologically insoluble biophysically specific β-sheet rich structures formed by the aggregation of misfolded proteins. In vivo tissue amyloid formation is responsible for more than 30 different disease states in humans and other mammals. One of these, Alzheimer’s disease (AD), is the most common form of human dementia. Amyloid fibril formation by the amyloid β-peptide (Aβ) is considered to be an underlying cause of AD, and strategies designed to reduce Aβ production and/or its toxic effects are being extensively investigated in both laboratory and clinical settings. Transthyretin (TTR) and proteins containing a BRICHOS domain are etiologically associated with specific amyloid diseases in the CNS and other organs. Nonetheless, it has been observed that TTR and BRICHOS structures are efficient inhibitors of Aβ fibril formation and toxicity in vitro and in vivo, raising the possibility that some amyloidogenic proteins, or their precursors, possess properties that may be harnessed for combating AD and other amyloidoses. Herein, we review properties of TTR and the BRICHOS domain and discuss how their abilities to interfere with amyloid formation may be employed in the development of novel treatments for AD.